2017
DOI: 10.1371/journal.pone.0169211
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Self-Reported Diabetes in the Australian National Eye Health Survey

Abstract: ObjectiveTo present the prevalence of self-reported diabetes in Indigenous and non-Indigenous participants in the National Eye Health Survey.Research Design and Methods3098 non-Indigenous Australians aged 50–98 years and 1738 Indigenous Australians aged 40–92 years were examined in 30 randomly selected sites, stratified by remoteness. A history of diabetes was obtained using an interviewer-administered questionnaire.Results13.91% (431/3098) of non-Indigenous Australians and 37.11% (645/1738) of Indigenous Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
1
12
1
1
Order By: Relevance
“…The prevalence of diabetes observed in older Malaysians aged 60 years and over is lower than the finding reported by the study in Australia. The prevalence of self-reported diabetes in a sample of Indigenous Australians aged 40-92 years was 37.11% [24]. However, the prevalence of self-reported diabetes in our study was higher than what has been documented by a Brazilin study, wherein 15.4% of the sample presented selfreported diabetes [29].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The prevalence of diabetes observed in older Malaysians aged 60 years and over is lower than the finding reported by the study in Australia. The prevalence of self-reported diabetes in a sample of Indigenous Australians aged 40-92 years was 37.11% [24]. However, the prevalence of self-reported diabetes in our study was higher than what has been documented by a Brazilin study, wherein 15.4% of the sample presented selfreported diabetes [29].…”
Section: Discussioncontrasting
confidence: 82%
“…The self-reported method was used to assess previously diagnosed diabetes by asking respondents, "Have you ever been told by a doctor that you had diabetes?. The self-reported diagnosis of diabetes has been found as a valid method to assess diabetes in epidemiological studies [23][24][25].…”
Section: Diabetesmentioning
confidence: 99%
“…The factors associated with DM in São Luís were similar to those found in other population-based studies [6,10,27,28,29]. The present study showed a self-reported DM prevalence is almost twice as high in women when compared to men.…”
Section: Discussionsupporting
confidence: 89%
“…The migrant population is believed to keep increasing in different countries; their heterogeneity becomes apparent with respect to the differences in the prevalence of diseases 7. Prevalence is likely to increase therefore, these findings can be used to inform future policy, planning and funding allocation to assist in controlling as well as managing different conditions 22…”
Section: Discussionmentioning
confidence: 99%